Impact of grassland management regimes on bacterial endophyte diversity differs with grass species. (9th March 2016) - Wemheuer, F.; Wemheuer, B.; Kretzschmar, D.; Pfeiffer, B.; Herzog, S.; Daniel, R.; Vidal, S.
Abstract: Most plant species are colonized by endophytic bacteria. Despite their importance for plant health and growth, the response of these bacteria to grassland management regimes is still not understood. Hence, we investigated the bacterial community structure in three agricultural important grass species Dactylis glomerata L., Festuca rubra L. and Lolium perenne L. with regard to fertilizer application and different mowing frequencies. For this purpose, above‐ground plant material was collected from the Grassland Management Experiment (GrassMan) in Germany in September 2010 and 2011. DNA was extracted from surface‐sterilized plant tissue and subjected to 16S rRNA gene PCRs. Endophytic community structures were assessed by denaturing gradient gel electrophoresis (DGGE)‐based analysis of obtained PCR products. DGGE fingerprints revealed that fertilizer application significantly altered the endophytic communities in L. perenne and F. rubra but not in D. glomerata . Although no direct effect of mowing was observed, mowing frequencies in combination with fertilizer application had a significant impact on endophyte bacterial community structures. However, this effect was not observed for all three grass species in both years. Therefore, our results showed that management regimes changed the bacterial endophyte communities, but this effect was plant‐specific and varied over time. Significance and Impact of the Study: Endophytic bacteria play an important role in plant health and growth. However, studies addressing the influence of grassland management regimes on these bacteria in above‐ground plant parts are still missing. In this study, we present first evidence that fertilizer application significantly impacted bacterial community structures in three agricultural important grass species, whereas mowing had only a minor effect. Moreover, this effect was plant‐specific and thus not visible for all grass species in each year. Consequently, this study sheds new light into the complex interaction of microbes and plants. Abstract : Significance and Impact of the Study: Endophytic bacteria play an important role in plant health and growth. However, studies addressing the influence of grassland management regimes on these bacteria in above‐ground plant parts are still missing. In this study, we present first evidence that fertilizer application significantly impacted bacterial community structures in three agricultural important grass species, whereas mowing had only a minor effect. Moreover, this effect was plant‐specific and thus not visible for all grass species in each year. Consequently, this study sheds new light into the complex interaction of microbes and plants.